Strotihypera, a new Old World genus of the tribe Elaphriini (Lepidoptera, Noctuidae, Noctuinae) - Kononenko, Vladimir S.; Han, Hui-Lin (Zootaxa, 2011)
A new genus Strotihypera gen. n. (type-species Erastria flavipuncta Leech, 1889) is described in the tribe Elaphrriini, subfamily Noctuini from the Eastern Palaearctic. The new combination Strotihypera flavipuncta (Leech, 1889) comb. n. is introduced for Hyperstrotia flavipuncta (Leech, 1889) A review of the Old World genera Strotihypera, Elaphria and Galgula of the tribe Elaphriini is presented.